New methods for the construction of fluorinated cyclic amines and amides - Charlesworth, Natalie (2022)
In recent years, photoredox catalysis has emerged as a powerful tool for the synthesis of complex building blocks. Fluorine-containing saturated nitrogen heterocycles are desirable structures in medicinal and biological chemistry, as the incorporation of fluorine can be used to influence key properties of a compound such as conformation, basicity and bioavailability. This thesis explores the utilisation of a photoredox-catalysed cyclisation/hydrogen atom transfer reaction of bromodifluoroethylamines, using a modular, two-step approach.